2009
DOI: 10.1021/ic901328v
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Personalized Solar Energy

Abstract: Personalized energy (PE) is a transformative idea that provides a new modality for the planet’s energy future. By providing solar energy to the individual, an energy supply becomes secure and available to people of both legacy and non-legacy worlds, and minimally contributes to increasing the anthropogenic level of carbon dioxide. Because PE will be possible only if solar energy is available 24 hours a day, 7 day a week, the key enabler for solar PE is an inexpensive storage mechanism. HX (X = halide or OH−) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
343
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 376 publications
(355 citation statements)
references
References 171 publications
7
343
0
Order By: Relevance
“…S16 and S17. The greater kinetic facility of the Ni II/I reduction relative to the Co II/I reduction is attributed to the requisite dissociation of a solvent [k°E T = 0.01 cm/s (36)] ligand that is axially coordinated to the low-spin d 7 Co II molecule as observed in the solid-state (32). No axial ligand is expected from our theoretical computations nor observed in the solid-state structure ( Fig.…”
Section: Significancementioning
confidence: 70%
See 1 more Smart Citation
“…S16 and S17. The greater kinetic facility of the Ni II/I reduction relative to the Co II/I reduction is attributed to the requisite dissociation of a solvent [k°E T = 0.01 cm/s (36)] ligand that is axially coordinated to the low-spin d 7 Co II molecule as observed in the solid-state (32). No axial ligand is expected from our theoretical computations nor observed in the solid-state structure ( Fig.…”
Section: Significancementioning
confidence: 70%
“…Efficient catalysis of transformations of energy consequence (7)(8)(9)(10)(11)(12)(13) mandates the coupling of electron transfer (ET) to proton transfer (PT) in proton-coupled electron transfer (PCET) reactions (14)(15)(16)(17)(18)(19)(20). In the absence of PCET, intermediates possessing equilibrium potentials that are prohibitively large depreciate the storage capacity offered by the solarto-fuels conversion process.…”
mentioning
confidence: 99%
“…However, the mechanism does not seem to belong to the "all concerted" category, the role of the acid being rather to inhibit a homolytic cleavage pathway (22). It has also been recently reported that the presence of a proximal acid group favors the production of water over hydrogen peroxide in the reduction of dioxygen by cobalt corrole complexes (13,23).…”
mentioning
confidence: 99%
“…We address, in the present contribution, reactions in which electron transfer is accompanied both by bond cleavage and proton transfer, which may also be first steps of multielectron processes. Contemporary energy challenges do involve such types of reactions, concerning particularly the cleavage of oxygen-oxygen and carbon-oxygen bonds (13).…”
mentioning
confidence: 99%
“…energy storage | solar energy | solar fuel | buried junction W ater splitting is the central chemistry that underlies the storage of solar energy in the form of chemical fuels because it delivers hydrogen from a renewable source (1)(2)(3). Direct solarto-fuels conversion can be achieved by interfacing suitable catalysts that carry out two separate half-reactions of water splittingthe four electron-four proton oxidation of water to O 2 and the two electron two-proton reduction of the produced protons to H 2 -to a photovoltaic (PV) material.…”
mentioning
confidence: 99%